Spiral polyethylene tube solar collectors performance analyzed by a new partially linear regression model - Vasconcelos, Julio C. S.; dos Santos, Denize P.; Brandão, Fernando J. B. [UNESP]; Ortega, Edwin M. M.; Biaggioni, Marco A. M. [UNESP]; Cordeiro, Gauss M. (Springer Nature, 2022)
Drying is considered one of the stages of the greatest energy expenditure in grain production. And from a financial standpoint, this practice remains costly for small farmers. This study aims to evaluate the efficiency of a spiral polyethylene tube solar collector prototype (which has been tested under three different conditions) destined to heating air for agro-industrial activity for small rural properties, using a new regression model based on the extension of the normal distribution. The results indicate that the solar collectors in the three conditions present significant differences, and the solar collector with glass cover has the highest average outlet temperatures. Also, significant differences occur for the average temperature readings performed at distances of 5, 10, 20 and 25 m along the polyethylene tube. The best thermal performance of the polyethylene tube solar collector is achieved for a 20-m-long tube. The new modeling can be considered as an alternative tool for sustainable energy data analysis.
Keywords: Cubic smoothing splines; Energy efficiency; Renewable energy; Simulation study